The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1128/mcb.21.2.414-424.2001
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6-Induced STAT3 and AP-1 Amplify Hepatocyte Nuclear Factor 1-Mediated Transactivation of Hepatic Genes, an Adaptive Response to Liver Injury

Abstract: Following hepatic injury or stress, gluconeogenic and acute-phase response genes are rapidly upregulated to restore metabolic homeostasis and limit tissue damage. Regulation of the liver-restricted insulin-like growth factor binding protein 1 (IGFBP-1) gene is dramatically altered by changes in the metabolic state and hepatectomy, and thus it provided an appropriate reporter to assess the transcriptional milieu in the liver during repair and regeneration. The cytokine interleukin-6 (IL-6) is required for liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
116
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 66 publications
4
116
0
1
Order By: Relevance
“…During liver regeneration, liver cells are exposed to stresses associated with functional deficiency, and these stresses ultimately lead to cell proliferation (9,19,20). We have identified 19 immediate-early transcription-factor genes that are differentially regulated during the priming phase (Table 1), many of which overlap with previously established immediate-early genes implicated by Taub and coworkers (8,15) and Fausto and coworkers (3,(10)(11)(12) that have established the importance of inflammation and protooncogenes in the early stages of liver regeneration.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…During liver regeneration, liver cells are exposed to stresses associated with functional deficiency, and these stresses ultimately lead to cell proliferation (9,19,20). We have identified 19 immediate-early transcription-factor genes that are differentially regulated during the priming phase (Table 1), many of which overlap with previously established immediate-early genes implicated by Taub and coworkers (8,15) and Fausto and coworkers (3,(10)(11)(12) that have established the importance of inflammation and protooncogenes in the early stages of liver regeneration.…”
Section: Resultsmentioning
confidence: 62%
“…In addition, we observed up-regulation of the insulin-like growth factor-binding protein (IGFBP-1), which is induced by IL-6 and HGF, and is known to be up-regulated during the course of liver regeneration (59). IGFBP-1 shares common promoter elements with other hepatic genes associated with the maintenance of metabolic homeostasis following large functional deficiency after PHx such as G6Pase (20).…”
Section: Extracellular Matrix͞cell Structure-and Membrane-associated mentioning
confidence: 80%
“…These include binding sites for chicken ovalbumin upstream promoter-transcription factor and hepatocyte nuclear factor-1. Both of these factors are expressed in the kidney (Baumhueter et al 1990, Suzuki et al 2000 and both have been previously shown to physically interact with members of the AP-1 transcription factor family (Leu et al 2001, Lin et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…In T cells, STAT proteins have been shown to physically and functionally interact with members of the Ets family of transcription factors over composite STAT-Ets DNA elements required for cytokine regulation of target genes (60,76). In hepatocytes, STAT3 was shown to cooperate with HFN1 in mediating the transcriptional response to interleukin 6 during liver regeneration (38).…”
mentioning
confidence: 99%